Opportunities and limitations for MICE tourism development in Łódź - Sylla, Marta; Chruściński, Jakub; Drużyńska, Paulina; Płóciennik, Paulina; Osak, Witold (Turyzm/Tourism, 2015)
Business tourism plays an important role in the tourism industry of Łódź. However, compared to other Polish cities relatively few MICE meetings are organised there. The purpose of this article is therefore to analyse the opportunities and limitations for MICE tourism development in Łódź compared to the city’s potential. The accommodation services, congress locations, accessibility by different means of transportation, and its image are the factors considered in the analysis. The results indicate the most important strategic actions that are recommended in order to improve the situation of business tourism in Łódź.